Differences in Career Anxiety of Senior High School Students by Gender: A Comparative Study in East Java - Nita Qonitaturrohmah; Henny Indreswari; Khairul Bariyyah; Nur Hidayah; Diniy Hidayaur Rahman (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2026)
Career anxiety is commonly experienced by high school students as they face increasing demands for educational and career planning. However, evidence regarding gender differences in career anxiety at the senior high school level, particularly in Indonesia, remains limited. This study aimed to examine the level of career anxiety among senior high school (or equivalent) students in East Java and determine whether significant differences exist based on gender. A quantitative comparative design was employed involving 128 students (36 males and 92 females) selected through cluster sampling from several senior high schools in East Java. Data were collected using a career anxiety scale with strong psychometric properties (Cronbach's Alpha = 0.927). The data were analyzed using normality and homogeneity tests followed by an Independent Samples t-test. The findings indicated that students generally experienced a moderate level of career anxiety. Female students obtained a slightly higher mean score (M = 79.95) than male students (M = 76.72); however, the difference was not statistically significant (t = -1.137, df = 126, p = .258). These findings suggest that gender is not a significant predictor of career anxiety among high school students. Instead, career anxiety may be more strongly influenced by individual factors, such as self-confidence and career readiness, as well as contextual support. Therefore, career guidance and counseling services should focus on strengthening career readiness, self-confidence, and career decision-making skills while providing equal support for all students regardless of gender.